Produktivitas Karyawan dalam Perspektif Beban Kerja, Motivasi Kerja, dan Lingkungan Kerja Islami: Studi Kasus pada PT Pos Indonesia KCU Madiun - Rahma Aprilina Aryanti; Fitra Rizal (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction/Main Objectives: Problems in work productivity often arise due to high workload and mismatch between the tasks faced and the competence of workers. This study aims to test and analyze the influence of workload, work motivation, and Islamic work environment on employee work productivity at PT Pos Indonesia KCU Madiun. Research Methods: The research employed a quantitative method using primary data collected directly from respondents. Data was gathered through questionnaires and analyzed using multiple linear regression. Finding/Results: The results of the study show that: (1) workload, work motivation, and Islamic work environment simultaneously influence employee work productivity at PT. Pos Indonesia KCU Madiun; (2) workload partially does not have a significant influence on employee work productivity; (3) while work motivation and Islamic work environment have a significant influence on employee work productivity at PT. Pos Indonesia KCU Madiun. Conclusion: The implications of these findings suggest that despite some significant constraints, productivity can still be improved. This indicates the importance of effective workload management, employee motivation programs to support performance, and innovation in the work environment.